Acetylcholinesterase Enzyme Inhibitor and Antioxidant Activities from A Mixture Extracts of Black Tea, Red Betel, Cinnamon and Curcuma - Huda, Aziz Syamsul; Hasan, Akhmad Endang Zainal; Safithri, Mega (IPB University, 2022)
Alzheimer's Disease (AD) is one of the consequences of impaired functioning of acetylcholine which can be hydrolyzed by the enzyme acetylcholinesterase. Alzheimer's treatment is carried out using two approaches, namely compounds (acetylcholinesterase inhibitors) and noncholinergics (antioxidants). There are commercial drugs that can slow the progression of Alzheimer's, but their use can cause excessive side effects. The use of herbal plants as a cure for Alzheimer's disease has been proven to be safer and does not cause excessive side effects. Herbal plants that can be used and developed are black tea, red betel, curcuma, and cinnamon. This study determined that extracts of black tea, red betel leaf, curcuma, and cinnamon's formula have the best antioxidant activity and level of inhibition of the acetylcholinesterase enzyme. F1 (cinnamon), F5 (cinnamon, black tea, red betel, and curcuma), F6 (cinnamon and black tea), and F11 (cinnamon, black tea, and curcuma) were the best formulations in each type of sample based on inhibitory AChE enzymes and antioxidants activity. F1 (cinnamon) is the most effective extract out of all formulations analyzed in this study. Keywords: Acetylcholinesterase; Alzheimer; Black Tea; Cinnamon; Red Betel; Curcuma